Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea - Peris-Felipo, Francisco Javier; Stigenberg, Julia; Quicke, Donald L.j.; Belokobylskij, Sergey A. (Zootaxa, 2019)
A revision of all Oriental species of subgenus Patrisaspilota Fischer, 1995 of the genus Orthostigma Ratzeburg, 1844 is provided and a new species from Papua New Guinea, Orthostigma (Patrisaspilota) enduwaense sp. nov., is described and illustrated. The species name Patrisaspilota memorandum Fischer, 1995 is synonymized with Orthostigma multicarinatum Tobias, 1990. A comprehensive key to the World Patrisaspilota species is presented and all known species are re-described and illustrated.